THE SUFISTIC HADITH THOUGHT OF HAMDANI BAKRAN ADZ-DZAKIEY: THE INTEGRATION OF SPIRITUAL HEALTH IN MODERN LIFE - Dzikri Nirwana; Hanafi Hanafi; Najib Irsyadi; Saifuddin Saifuddin; Tri Hermawan Aini (STAI Asy-Syukriyyah, 2026)
This study examines Hamdani Bakran adz-Dzakiey’s thought in Prophetic Intelligence, which offers a Sufi-psychological approach to Hadith interpretation. Utilizing a qualitative-descriptive method with an interdisciplinary framework (Hadith Studies and Islamic Psychology), this research analyzes how Hadith is transformed into an instrument for spiritual health. The findings reveal that Hamdani positions Prophet Muhammad PBUH as the prototype of prophetic intelligence through a dual-layered interpretation: exoteric (linguistic and legal analysis) and esoteric (inward meaning for soul purification). Distinguishing himself from textualist trends, Hamdani contextualizes Hadiths on aqidah and sharia as foundations for spiritual well-being. This interpretive pattern demonstrates a methodological distinction that bridges formal text with spiritual depth, ensuring relevance for modern mental development. As a Sufi practitioner, Hamdani successfully integrates Hadith authority into spiritual counseling without neglecting the exoteric meaning, providing a holistic framework for contemporary spiritual-psychological health.